Human Fanconi anemia monoubiquitination pathway promotes homologous DNA repair - Nakanishi, Koji (National Academy of Sciences, 2005)
Fanconi anemia (FA) is a recessive disorder characterized by congenital abnormalities, progressive bone-marrow failure, and cancer susceptibility. Cells from FA patients are hypersensitive to agents that produce DNA crosslinks and, after treatment with these agents, have pronounced chromosome breakage and other cytogenetic abnormalities. Eight FANC genes have been cloned, and the encoded proteins interact in a common cellular pathway. DNA-damaging agents activate the monoubiquitination of FANCD2, resulting in its targeting to nuclear foci that also contain BRCA1 and BRCA2/FANCD1, proteins involved in homology-directed DNA repair. Given the interaction of the FANC proteins with BRCA1 and BRCA2, we tested whether cells from FA patients (groups A, G, and D2) and mouse Fanca(–/–) cells with a targeted mutation are impaired for this repair pathway. We find that both the upstream (FANCA and FANCG) and downstream (FANCD2) FA pathway components promote homology-directed repair of chromosomal double-strand breaks (DSBs). The FANCD2 monoubiquitination site is critical for normal levels of repair, whereas the ATM phosphorylation site is not. The defect in these cells, however, is mild, differentiating them from BRCA1 and BRCA2 mutant cells. Surprisingly, we provide evidence that these proteins, like BRCA1 but unlike BRCA2, promote a second DSB repair pathway involving homology, i.e., single-strand annealing. These results suggest an early role for the FANC proteins in homologous DSB repair pathway choice.